Iso-alpha acids from hops (Humulus lupulus) inhibit hepatic steatosis, inflammation, and fibrosis - Mahli, Abdo; Koch, Andreas; Fresse, Kim; Schiergens, Tobias; Thasler, Wolfgang Erwin; Schoenberger, Christina; Bergheim, Ina; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Laboratory Investigation, 2018)
Non-alcoholic fatty liver disease (NAFLD) is considered to be the hepatic manifestation of the metabolic syndrome. Iso-alpha acids (IAAs), hop-derived bitter compounds in beer, have been shown to beneficially affect different components of the metabolic syndrome such as insulin resistance and dyslipidemia. However, IAAs have not yet been studied in the context of chronic liver disease. Here we analyzed the effect of IAA on the pathogenesis of NAFLD. Once, we applied IAA to mice in combination with a NAFLD-inducing Western-type diet (WTD), and observed that IAA significantly inhibited WTD-induced body weight gain, glucose intolerance, and hepatic steatosis. Fitting to this, IAA dose-dependently inhibited cellular lipid accumulation in primary human hepatocytes (PHH) in vitro. Reduced expression of PPAR-gamma and key enzymes of lipid synthesis as well as increased expression of PPAR-alpha, indicative for increased lipid combustion, were identified as underlying mechanisms of reduced hepatocellular steatosis in vitro and in vivo. Analysis of hepatic HMOX1 expression indicated reduced oxidative stress in IAA-treated mice, which was paralleled by reduced activation of the JNK pathway and pro-inflammatory gene expression and immune cell infiltration. Furthermore, IAA reduced hepatic stellate cell (HSC) activation and pro-fibrogenic gene expression. Similarly, IAA also dose-dependently reduced oxidative stress and JNK activation in steatotic PHH, inhibited HSC activation, and reduced proliferation and pro-fibrogenic gene expression in already activated HSC in vitro. In conclusion, IAAs inhibit different pathophysiological steps of disease progression in NAFLD. Together with previous studies, which demonstrated the safety of even long-term application of IAA in humans, our data suggest IAA as promising therapeutic agent for the prevention and treatment of (non)alcoholic (fatty) liver disease.
EVALuna2:35807